2015
DOI: 10.1002/ange.201507152
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische stereoselektive Dihalogenierung von Alkenen: Herausforderungen und Chancen

Abstract: Während in den letzten Jahren signifikante Fortschritte bei der Entwicklung katalytischer, enantioselektiver Halogenfunktionalisierungen von Alkenen erzielt wurden, ist die verwandte Dihalogenierung von Olefinen zur Bildung enantiomerenangereicherter vicinaler dihalogenierter Produkte vergleichsweise unterentwickelt. Allerdings verweist die steigende Anzahl komplexer Naturstoffe mit Halogenatomen an stereogenen Zentren deutlich auf diese Lücke im Arsenal der Synthesechemie. Dieser Aufsatz behandelt die Herausf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 341 publications
(304 reference statements)
0
3
0
Order By: Relevance
“…Existing data implicate radical intermediates (Scheme 5b). In particular,w hen styrene was exposed to CCl 4 and CBr 4 in the presence of [ClRh(DIOP)],w eo btained the cross-over product 1a along with the expected product 1x [Eq. (1)].A tc ryogenic temperatures,b enzyl chloride formation is not observed, but the generation of 1asuggests that the CCl 3 radical was generated.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Existing data implicate radical intermediates (Scheme 5b). In particular,w hen styrene was exposed to CCl 4 and CBr 4 in the presence of [ClRh(DIOP)],w eo btained the cross-over product 1a along with the expected product 1x [Eq. (1)].A tc ryogenic temperatures,b enzyl chloride formation is not observed, but the generation of 1asuggests that the CCl 3 radical was generated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[2] More broadly,f ree radicals are prized intermediates in organic synthesis because they possess exceptional reactivity,a lthough control of that reactivity remains difficult. [3] In this context, the development of an enantioselective Kharasch addition reaction appeared valuable for both practical and fundamental reasons.I tw ould provide optically active alkyl halides, [4] and the trihalomethyl group finds utility as am etabolically stable replacement for À CH 3 groups.F inally,a na symmetric platform for the Kharasch addition reaction could potentially be expanded to other CÀX(X= halide) and XÀY(Y= SR, NR 2 )reagents.…”
mentioning
confidence: 99%
“…[4] In a highly instructive review, Denmark analysed the scope and limitations of enantioselective trans ‐addition of dihalides to alkenes and outlined the advances concerning the attempts to achieve a cis ‐addition. [5] In an exceptional investigation, the Denmark group demonstrated that the cis ‐chlorination of alkenes can be realised (Scheme 1 ) utilising an oxidising agent ( 3 ), a simple selenium‐based catalyst, such as diphenyldiselenide, and a quenching agent (Me 3 SiCl) to remove potentially nucleophilic fluoride anions from the reaction mixture. [6] The role of the pyridine‐ N ‐oxide derivative 4 was reported to enhance the rate of the reaction but was omitted in following reports.…”
mentioning
confidence: 99%